Phase Evolution and Li Diffusion in LATP Solid‐State Electrolyte Synthesized via a Direct Heat‐Cycling Method. Issue 8 (31st May 2022) - Ashton, Thomas E.; Baker, Peter J.; Shakespeare, Yiana S.; Commandeur, Daniel; Darr, Jawwad A.
Abstract : Herein, the direct synthesis of phase‐pure lithium aluminum titanium phosphate (Li1.3 Al0.3 Ti1.7 (PO4 )3, LATP) solid‐electrolyte powder in 220 min and relatively low temperatures (850 °C) is achieved via a new (cyclic) fast heat treatment (c‐FHT) route. The complex structural evolution highlights rate‐limited lithium incorporation of intermediate metal phosphates formed prior to the final phase‐pure LATP. The prepared LATP product powder displays similar bulk (2 × 10 −10 cm 2 s −1 ) and local (3 × 10 −10 cm 2 s −1 ) values for lithium diffusion coefficients ( D Li ) characterized by electrochemical impedance spectroscopy and muon spin relaxation (μSR), respectively. The similarity between both D Li values suggests excellent retention of inter‐ and intraparticle lithium diffusion, which is attributed to the absence of deleterious surface impurities such as AlPO4 . A low‐energy barrier ( E a = 73 meV) of lithium diffusion is also estimated from the μSR data. Abstract : Using a new cyclic fast heat treatment (c‐FHT) methodology, single‐phase lithium aluminium titanium phosphate (Li1.3 Al0.3 Ti1.7 (PO4 )3, LATP) powder has been synthesized in faster times and lower temperatures. Exceptional bulk (2 × 10 −10 cm 2 s −1 ) and local (3 × 10 −10 cm 2 s −1 ) diffusion coefficients are estimated by state‐of‐the‐art muon spin relaxation (μSR). Rate‐limiting processes during c‐FHT are identified using multiphase Rietveld refinement.